Technological parks as a mechanism for the implementation of innovation policy of the state - Maltseva, S.V.; Piddubna, O.A.; Khomenko, Ya.V. (Економічний вісник Донбасу, 2010)
The article presents the concept of technopark, his primary purposes and tasks. The indicators of technopark’s activity in Ukraine are analyzed. Urgency of creation of technological parks for maintenance of a sustainable development of economy of Ukraine is proved. Key words: technological park, innovation activity, investments, investor, high technological production, export potential.